Exploring Causes of Plagiarism and Its Reduction among Students - Pohanwal Zarghona Achekzai (RIRAI Publisher, 2024)
This research focused on causes of plagiarism among students and its reduction. Through qualitative research related to the first question that what is students’ understanding about plagiarism? How can they define the word of plagiarism? It is found that all the students have the same understanding of the meaning of the word of plagiarism and they defined it in different ways with same meaning they mentioned that it is taking of others work, idea or activity and name it as their own work. Related to the second question of the questionnaires that what type of plagiarism do the students familiar with? Different kinds of plagiarism found out through research namely intentionally, unintentionally, direct, self, accidental and source based on plagiarism. Related to the third question that what causes students’ plagiarism? it is found that there are different causes of plagiarism such as lack of content knowledge, having some problem on citation, references, lack of information, lack of enough ability how to do something, lack of hard working, academic pressure, fear of not to be succeed or have low grades in the exam are causes for their plagiarism. Related to the fourth question of the research on how plagiarism can be reduced among students? It is found that through giving good resources and lectures regarding research methodology section, hiring professionals, updating research methodology subjects and students should be taught and trained practical knowledge of the content of the research paper and teachers should have regular meeting with students related to their assignment. Related to the fifth question that what is instructor’s penalty for the students who plagiarize? It is found that teacher will not accept the assignment of the students and they will ask students to re- do it and if he/ she fined two students with the same paper or paragraphs he will reduce the grade for both of the students.